2019
DOI: 10.1128/jcm.01344-19
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Clinically Meaningful Antibiotic Concentrations on Recovery of Escherichia coli and Klebsiella pneumoniae Isolates from Anaerobic Blood Culture Bottles with and without Antibiotic Binding Resins

Abstract: Blood cultures are routinely collected in pairs of aerobic and anaerobic bottles. Artificial sterilization of Gram-negative bacteria in aerobic bottles containing clinically meaningful antibiotic concentrations has previously been observed. This study assessed recovery from anaerobic bottles with and without antibiotic binding resins. We studied the recovery of Escherichia coli and Klebsiella pneumoniae when exposed to meropenem, imipenem, cefepime, cefazolin, levofloxacin, and piperacillin-tazobactam in resin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…It is worth noting that the anaerobic bottles contained different media, which could influence the recovery of many pathogens, especially when exposed to antimicrobial agents. 10 In addition, the resin-free BACTEC Lytic/10 Anaerobic/F bottle evaluated here is the only type of BD anaerobic blood culture media approved by the Chinese National Medical Products Administration (NMPA), which to some extent has lead to the relative lower positive rate of BACTEC system. In comparison, the resin-free BacT/ALERT SN anaerobic bottles that functioned to ensure the activities of antimicrobials involved showed 0/48 (0.0%) recovery when evaluated with antimicrobial agents at peak serum concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that the anaerobic bottles contained different media, which could influence the recovery of many pathogens, especially when exposed to antimicrobial agents. 10 In addition, the resin-free BACTEC Lytic/10 Anaerobic/F bottle evaluated here is the only type of BD anaerobic blood culture media approved by the Chinese National Medical Products Administration (NMPA), which to some extent has lead to the relative lower positive rate of BACTEC system. In comparison, the resin-free BacT/ALERT SN anaerobic bottles that functioned to ensure the activities of antimicrobials involved showed 0/48 (0.0%) recovery when evaluated with antimicrobial agents at peak serum concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…However, it should be noted that the bacterial inoculum (50 to 100 CFU per bottle) used by Menchinelli et al. (2019b) was much higher than the inoculum (7 to 30 CFU per bottle) used by Chen et al. (2019) , and this difference might have caused the dissimilar performance of BC bottles observed in the two studies.…”
Section: Discussionmentioning
confidence: 92%
“…Similarly, our previous study (albeit in the adult setting) showed no recovery for E. coli when tested in the presence of meropenem at the lowest but clinically relevant concentration in both BacT/Alert (FA Plus and FN Plus) and Bactec (Plus Aerobic/F and Plus Anaerobic/F) bottles ( Menchinelli et al., 2019b ). Concomitantly, Chen et al. (2019) showed that the recovery of E. coli exposed to meropenem midpoint and trough concentrations was more successful in BacT/Alert FN Plus bottles than in Bactec Plus Anaerobic/F bottles.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Resins can neutralize select antibacterial agents (including common empirically utilized antibiotics such as piperacillin-tazobactam, vancomycin, and some cephalosporins), but have lower to no ability to neutralize other agents (eg, carbapenems and fluoroquinolones). 1 , 2 , 3 Resins improve the yield of blood cultures for patients who are on antibiotics at the time of blood collection; this has clear advantages for initial blood cultures but also results in more positive cultures for patients subsequently on therapy, and thus more laboratory expense. The clinical significance of subsequent positive cultures in bottles with resins is unclear.…”
Section: Selection Of Media and Additive Types For Blood Culturementioning
confidence: 99%